Nitrogen sidedressing on common bean cultivated in no-tillage system on different vegetal covers - Silva, Tiago Roque Benetoli da (2009)
The present work had as objective to evaluate the effect of application or not of nitrogen in covering on “water” beans, cultivated under different vegetal covers. The experiment was carried out in Campo Grande, Mato Grosso do Sul State, Brazil. The experimental design was randomized blocks in an split-plot outline scheme, with four repetitions. The parcels were constituted by different vegetal covers (high density maize, cotton and wheat) and subparcels by nitrogen sidedressing application (0 and 70 kg ha-1). Bean sowing (Carioca Precocious) was carried out in September, 2005. The following evaluations were conducted: cycle, plant population, components, mass of 100 grains, yield, dry matter and grain crude protein. It can be concluded that bean yield was increased when cultivated after wheat culture, and that nitrogen fertilization in covering increased yield.